Influence of Dimethylsulfoxide and Dioxygen in the Fructose Conversion to 5-Hydroxymethylfurfural Mediated by Glycerol's Acidic Carbon - Tudino, Tatiane C.; Nunes, Renan S.; Mandelli, Dalmo; Carvalho, Wagner A. (Frontiers in Chemistry, 2020)
Both the catalytic production of 5-hydroxymethylfurfural (5-HMF) from carbohydrates and the use of a catalyst obtained from residues stand out for adding value to by-products and wastes. These processes contribute to the circular economy. In this work, it was evaluated optimized conditions for 5-HMF production from fructose with high yield and selectivity. The reaction was catalyzed by an acidic carbon obtained from glycerol, a byproduct of the biodiesel industry. Special attention has been given to the use of dimethyl sulfoxide (DMSO) as a solvent and its influence on system activity, both in the presence and absence of O2. The results indicated that a solid with acidic properties can be easily and quickly obtained from a glycerol carbonization process in the presence of sulfuric acid. Amounts of total acidic groups as high as 4.2 mmol/g were obtained after 15 min. The use of this catalyst in fructose dehydration allowed achieving conversions close to 100% with 5-HMF selectivities higher than 90%. However, the influence of DMSO in the presence of O2 should be considered, as the stabilization of a reaction intermediate by the [O2: DMSO] complex is favored and, both fructose conversion and 5-HMF yield increase.